Origin and evolution of intercrystalline brine in the northern Qaidam Basin based on hydrochemistry and stable isotopes - Ren, Qianhui; Li, Binkai; Zhang, Yan; Wu, Haitao (Frontiers in Environmental Science, 2023)
The Kunteyi basin, located in the northern Qaidam, is known as a significant potash deposition in China. In order to support the exploitation of potassium salt, it is of great significance to study the origin of the potassium-rich intercrystalline brine. The chemical and isotopic data of the intercrystalline brine is used in this study to analyze the evolution process of the brine. According to the relationship between H and O isotopes, atmospheric precipitation is the primary source of water in brine. Both the CNa/CCl vs TDS and CNa/CCl vs CBr/ CCl plot near the halite dissolution line, which indicates halite dissolution is the major salinity source. The CNa/CCl ratio, Cl/(Na+K+Mg) ratio, and cluster analysis suggest the occurrence of polyhalite dissolution in the study area. The positive δ¹¹B value, the larger δ¹¹B isotope values and smaller Ca2+ concentrations compared with potassium lake water suggested the influence of hydrothermal fluids. The thermal water recharged the Pleistocene layer， reacted with polyhalite, and formed Mg-and K-rich brine. The solution rises along the channel formed by the fracture and is supplied to the shallow intercrystalline brine.